Pengendalian Hama Ulat Api (Setora nitens) dengan Menggunakan Bahan Aktif Deltametrin dan Ekstrak Daun Mimba - Febri Antoni Simanjuntak (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
Oil palm is one of the plantation crops that has an important role for the national economy,especially as a provider of employment and a source of foreign exchange income. Areas that havethe potential for expansion of oil palm plantations are not only mineral lands, but also peatlands,scrublands, alang-alang lands, and primary forest lands. Setora nitens is one of the main pests thatattack oil palm plants and includes caterpillars which are dominant in oil palm plantations.S.nitens caterpillars attack oil palm plants by eating the leaves so that the leaves are damaged andonly the leaves are left. This research was conducted to see the mortality rate of the caterpillarsusing the active ingredient deltamethrin and neem leaf extract. This study used MS.Exel bycalculating the Trial average test using two factors, namely the first factor (Deltamethrin) andneem leaf extract with three treatment levels, namely Control (D0), Deltametrin 20 cc / liter (D1),and Deltamethrin 40 cc / Liter ( D2). The second factor (neem leaf extract) with three levels oftreatment, namely control (N0), neem leaf extract 50 cc / liter (N1), and neem leaf extract 100 cc /liter (N2). Deltamethrin pesticides and neem leaf extract in D2N1 treatment with a dose of 40 mldeltamethrin and 50 cc of neem leaf extract were more effective and efficient in controlling fireworms.